Optical spectrum of HDE 245770 /A0535 + 26/ - R. A. Wade; J. B. Oke (The Astrophysical Journal, 1977)
Urinary tract infections are one of the most common infectious diseases, with Escherichia coli as the predominant pathogen. Traditional diagnostic methods fail to meet clinical demands for rapid and specific detection. Here, we developed an efficient urine E. coli detection strategy via a reporter phage cocktail. Four reporter phages (T2::Nluc, T4::Nluc, T5::Nluc, T6::Nluc) were constructed by the CRISPR/Cas9 system combined with homologous recombination. One-step growth curves, optimal multiplicity of infection, and lytic efficiency showed that the Nluc gene block insertion exerted heterogeneous effects on phages. Luminescence assays demonstrated that all five reporter phages (including previously preserved T7::Nluc) and the cocktail offered favorable limits of detection (≥10 3 CFU/mL), high specificity, and no urine matrix interference. However, single phages exhibited limited coverage among 177 clinical E. coli isolates. But the reporter phage cocktail remedies this limitation. In large-scale clinical validation, the cocktail achieved sensitivity 73.15% (63.76%-81.22%), specificity 100.00% (99.53%-100.00%), positive predictive value (PPV) 100.00% (95.44%-100.00%), and negative predictive value (NPV) 96.42% (95.18%-97.36%) (all 95% confidence interval [CI]), and excellent concordance with the gold-standard method (Kappa = 0.83, 95% CI: 0.77-0.89), greatly outperforming single reporter phages (~40.00% sensitivity). This method requires no sample pretreatment, is simple to operate, and completes detection within 4 h, significantly improving diagnostic efficiency. Accordingly, it provides a novel platform for pathogen detection and supports the clinical translation of reporter phage diagnostics.IMPORTANCEUrinary tract infections impose substantial economic and public health burdens. In this study, we successfully constructed Escherichia coli-specific reporter phages T2::Nluc, T4::Nluc, T5::Nluc, and T6::Nluc. Combined with the previously preserved T7::Nluc, these phages formed a reporter phage cocktail. Co-cultivation of this cocktail with clinical samples enabled rapid and specific detection of E. coli in clinical urine, with a significantly shortened detection time (4 h) and good concordance with the gold-standard detection method (Kappa = 0.83), effectively improving detection efficiency and accuracy. This novel pathogen detection platform, integrating specific recognition and signal amplification, not only provides a new technical approach for the rapid and accurate diagnosis of clinical urinary tract infections but also effectively promotes the coordinated improvement of infectious disease diagnosis and treatment in terms of timeliness-precision-cost.